Music Variations as Alternative Media in Providing Light Indonesian Pentecostal Church, Banana Garden Assembly, Medan - Hendrik L Simanjuntak; Zk Pangaribuan; Hasiando Sihombing; Swilly Pakpahan; Bertin Pangapuli Sakoikoi; Saud Kiki Pandiangan; Rio Siburian (International Perspectives in Christian Education and Philosophy, 2025)
In Christianity there are various sects with diverse dogmas. When Christianity entered the Pematangsiantar area, various churches with different sect backgrounds grew and developed, such as the Catholic Church, Huria Kristen Batak Protestan (HKBP), Simalungun Protestant Christian Church (GKPS), Indonesian Christian Church (GKI), Indonesian Bethel Church (GBI), Indonesian Pentecostal Church (GPI), and others (Aritonang, 2008)